Analisis Illat Ribawi Menurut Empat Madzhab Fikih - Habibillah, Dovi iwan Musthofa; Hamdi, Muhammad (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
Business dynamics progress shows some data that lead to more riba for businessmen, even though this advancement succeeds the nation's economic development, but the illegality of riba is undeniable based on several verses in the Qur’an. This research aims to grasp four Madzhab Fiqh (Islamic law ideology) perspectives, particularly about the essence of illat ribawi wealth and the effect of its different views on riba transactions in Islamic economics. Library research is applied through this paper as a documentary is used for data collection while a content analysis technique is taken to analyze it. The paper results showed that there are various Islamic scholar’s perspectives about illat-ribawi on gold and silver which are classified as scale, ghalabah tsamaniyyah, and muthlaqutssamaniyyah. This article concludes that all of the Islamic law scholars agree that riba category works on six things which mentioned by the prophet’s tradition with different opinions about the illat.